Longitudinal impacts of greenness on cardiovascular disease conditions. (14th October 2021) - Brown, S C; Aitken, W; Lombard, J; Wang, K; Parrish, A; Nardi, M; Kardys, J; Szapocznik, J
Abstract: Introduction: Environmental determinants of health, such as greenness, play an increasing role in our understanding of cardiovascular disease, and can inform how to address geographic cardiovascular disparities. This study assesses the impact of greenness and changes in greenness on cardiovascular disease. Purpose: The purpose of this study is to investigate the impact of greenness and changes in greenness on cardiovascular disease diagnoses. Methods: The sample for this prospective, longitudinal study was comprised of 243, 558 U.S. Medicare beneficiaries 65 years or older, residing on the same Census Block from 2011 through 2016, and who had a Miami-Dade residential 9-digit zip code. Analyses examined the impact of greenness, measured by mean block-level Normalized Difference Vegetation index (NDVI) from satellite imagery to incidence of new cardiovascular conditions including: acute myocardial infarction, atrial fibrillation, heart failure, ischemic heart disease, hypertension, and stroke/ transient ischemic attack. Zero-inflated poisson regression was used to model the odds of developing any new cardiovascular disease and number of new cardiovascular conditions based on block level greenness while adjusting for individual age, gender, race/ethnicity, number of baseline cardiovascular conditions, and neighborhood characteristics including income and walkability. Results: Living in a higher greenness Census Block was associated with lower odds of having at least one new cardiovascular condition and having a small number of new conditions, adjusting for individual and neighborhood level characteristics. When compared to individuals living in the lowest tertile of greenness throughout the study, those individuals living in the highest tertile of greenness throughout the study had a 16% lower odds of having any new cardiovascular conditions (OR=0.84, 95% CI: 0.79–0.90, p<0.001) and among individuals developing at least one new cardiovascular disease, 4% fewer new cardiovascular conditions (OR=0.96, 95% CI: 0.92–0.99, p<0.05). When compared to individuals living in the lowest tertile of greenness throughout the study, those individuals living in areas that increased their greenness from the lowest tertile to the highest tertile of greenness had a 15% lower odds of having any new cardiovascular conditions (OR=0.85, 95% CI: 0.75–0.97, p<0.001) and among individuals developing at least one new cardiovascular disease, 9% fewer new cardiovascular conditions (OR=0.91, 95% CI: 0.83–0.99, p<0.05). Conclusions: High greenness is associated with lower rates of cardiovascular conditions over time, both when greenness increases and when a Census Block maintains high greenness. It is remarkable that these effects appear in five years, a relatively short amount of time for a positive environmental impact; and that even for those who began in the lowest greenness tertile, an increase to the high greenness tertile had a significant effect. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Robert Wood Johnson Evidence for Action Grant